Dynamics of the Cellular and Humoral Immune Response After BNT162b2 Messenger Ribonucleic Acid Coronavirus Disease 2019 (COVID-19) Vaccination in COVID-19-Naive Nursing Home Residents. (13th September 2021) - Van Praet, Jens T; Vandecasteele, Stefaan; De Roo, Anneleen; Vynck, Matthijs; De Vriese, An S; Reynders, Marijke
Abstract: Short-term humoral and cellular immune responses are diminished after BNT162b2 messenger ribonucleic acid coronavirus disease 2019 (COVID-19) vaccination in COVID-19-naive nursing home residents, a population particularly vulnerable to the disease. We found both responses to decline after 4 weeks and remain lower than those of healthcare workers after 24 weeks, with an estimated half-life of the antibody response of 47 days. At 4 weeks, older age was significantly associated with a decreased humoral response, and diabetes mellitus and active malignancy were associated with a decreased cellular response. Our results imply that COVID-19-naive nursing home residents are a target group for booster vaccination trials. Abstract : In COVID-19-naive nursing home residents, the humoral and cellular immune response after BNT162b2 mRNA COVID-19 vaccination declines after 4 weeks and remains lower than those of healthcare workers after 24 weeks.